Pusat Edukasi Daur Ulang Sampah Di Pekanbaru Dengan Pendekatan Arsitektur Organik - Elfina Widya Hastuti; Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The existence of The Recycling Education Center in Pekanbaru is supported by waste banks and compost houses that are not optimal, minimum appreciation of waste recycling works and scale of socialization targets. The Recycling Education Center has a function as a forum for training, production, and exhibition using the waste bank system to encourage people to sort and save waste. This method uses an Organic Architecture approach that has harmonization between the humans and the natural environment on a site and supports recycling. Organic Architecture principles that support recycling, which is energy-efficient, sustainable, and material. Through the concept of Recycle, buildings can adapt to climate conditions, reuse energy for operations, use harmless materials, form and arrange zones to represent a recycle symbol.keywords: Recycling Education Center, Pekanbaru, Organic Architecture